2020
DOI: 10.1186/s12913-020-4978-0
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life experience for older adults in Ireland: results from the Irish longitudinal study on ageing (TILDA)

Abstract: Background: End-of-life experience is a subject of significant policy interest. National longitudinal studies offer valuable opportunities to examine individual-level experiences. Ireland is an international leader in palliative and end-of-life care rankings. We aimed to describe the prevalence of modifiable problems (pain, falls, depression) in Ireland, and to evaluate associations with place of death, healthcare utilisation, and formal and informal costs in the last year of life. Methods: The Irish Longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Our paper highlights that even in a setting with well-established palliative care services, the risk of inappropriate prescribing among people with limited life expectancy in significant. However, these deficiencies in patient experience must be understood in the context of other challenges; previous research in TILDA demonstrated strong evidence for undermanagement of illness symptoms near end of life, whereas overprescribing is a form of overtreatment [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our paper highlights that even in a setting with well-established palliative care services, the risk of inappropriate prescribing among people with limited life expectancy in significant. However, these deficiencies in patient experience must be understood in the context of other challenges; previous research in TILDA demonstrated strong evidence for undermanagement of illness symptoms near end of life, whereas overprescribing is a form of overtreatment [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…TILDA-GRO linkage is scheduled for an update in 2022 and in future iterations we will update the model accordingly. TILDA collects usage across more than 20 categories of health care use 39 . We will incorporate all categories in future models, and then combine with unit costs for each category to model health care costs 40 .…”
Section: Discussionmentioning
confidence: 99%
“…CAPI and SCQ follow‐up occurs at each Wave; health assessments were conducted again at Wave 3. In the event of a participant death, TILDA approaches a family member or close friend to complete a voluntary interview on end‐of‐life experience; full details including ethical procedures have been provided previously 3 . This study uses data up to and including Wave 5 (2018).…”
Section: Methodsmentioning
confidence: 99%
“…To identify additional predictors we drew on Andersen's model of predisposing, enabling, need characteristics and prior utilisation 16 ; and prior cost modelling using TILDA data 3 . The full list of predictors is provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation